Anorectal manometry: Should it be performed in a seated position?. Issue 5 (1st December 2016) - Wu, G.‐j.; Xu, F.; Lin, L.; Pasricha, P. J.; Chen, J. D. Z.
Abstract: Background: Anorectal manometry (ARM) is typically preformed in a lateral position. This non‐physiological testing position has produced an unexpected negative rectoanal pressure gradient (RAPG, i.e. difference between rectal and anal pressure) with normal defecation. This study was designed (i) to study differences in ARM parameters between water‐perfused and solid‐state sensors and between lateral and seated positions and (ii) to investigate the roles of ARM parameters in predicting balloon expulsion. Methods: ARM was performed in 18 healthy volunteers (HV) and 60 patients with functional constipation (FC) under three randomized conditions: water‐perfused in lateral position, solid‐state in lateral position, and solid‐state in seated position, followed by a balloon expulsion test in seated position. Key Results: i) Under the same lateral position, solid‐state sensors produced higher rectal resting pressure and RAPG than water‐perfused sensors. ii) Using the solid‐state sensors, ARM in the seated position revealed higher resting rectal pressure (34.9 vs 10.9 mmHg in HV, 30.9 vs 10.6 mmHg in FC, both P <.001) and higher RAPG (22.6 vs −6.2 mmHg in HV, 17.1 vs −8.1 mmHg in FC, both P <.001) than the lateral position. iii) When ARM was performed using solid‐state sensors in seated position, RAPG was predictive of balloon expulsion; using 10 mmHg as a threshold, RAPG could predict balloon expulsion with specificity of 82% and sensitivity 77%. Conclusions and Inference: ARM performed in a seated position using solid‐state sensors seems more accurate in assessing rectal pressure, and the RAPG measured under these conditions is predictive of balloon expulsion in FC patients. Abstract : This study aimed to establish the validity and importance of performing anorectal manometry (ARM) in the physiological seated position instead of frequently used left lateral position. For this, we compared the differences in ARM parameters between water‐perfused and solid‐state sensors and between lateral and seated positions. The results showed that ARM performed in a seated position using solid‐state sensors seems most accurate in assessing rectal pressure, and rectoanal pressure gradient (RAPG) measured under these conditions is predictive of balloon expulsion.